Improving Hard Work And Students Achievement In Mathematics Learning By Using Contextual Teaching And Learning (Ctl) To Grade Vii A Of Smp Al-Islam 1 Surakarta For 2012/2013 Academic Year - Jumiati, Jumiati; , Rita P. Khotimah, S.Si., M.Sc (2013)
The objective of this research is to improve the hard work and student's achievement in learning mathematics grade VII A of SMP Al-Islam 1 Surakarta. This is an action research with the subject is the students grade VII A of SMP Al- Islam 1 Surakarta academic year 2012/2013 with the number of students is 24 students. The data is obtained from observation, field notes, documentation, and test. Technique of data analysis in this research includes data collection, data presentation, and data verification. The result of research are: 1) the hard work of students in learning mathematics are increase, include: a) before the treatment are given, there are 14 students (58,33%) who demonstrate seriousness in solve the problems, after the treatment there are 19 students (90,48%), b) before the treatment are given, there are 6 students (25%) who complete the problems on time, after the treatment there are 17 students (80,96%), c) before the treatment are given, there are 5 students (20,83%) who do not give up to solve the problems, after the treatment there are 18 students (85.71%), d) before the treatment are given, there are 5 (20,83%)students who solve the problem carefully and accurately, after the treatment there are 15 students (71.43%). 2) the students' achievement increase, it can be shown by: before the treatment are given, there are 5 students (20,83%) who scored above the passing grade, after the treatment there are 17 students (80,96%) who scored above the passing grade. So, it can be concluded that CTL strategy can improving the hard work and students' achievement in learning mathematics.